The Indian Government’s Environmental Stewardship: A Review of Pollution Control Efforts (Indian Journal of Social Science and Literature (IJSSL), 2024)
This paper is an attempt to get and make acquainted with the role that the Indian Government had/has played or is playing to curb the brisk expansion of pollution which is affecting human health and the environment drastically and disastrously. Different contamination types viz. Air Contamination, Water Contamination, Soil Contamination, Noise Contamination, Land Contamination, Photo Contamination etc. have brought immutable adverse changes in all sorts of lives existing to breathe in air, water and soil. In addition, the synthetic and natural non-living creations are also influenced detrimentally. The citizens of nation, whether educated or uneducated are at par responsible for destruction of every component of the environment. Worthless is not mentioning here the appreciable endeavors that the Government has put on its part through its policies that are framed, although not implemented with vigor on real grounds, to rein the outburst of pollution. National Ambient Air Quality Standards, National Air QualityMonitoring Programme, National Air Quality Index (AQI), Hari Diwali and Swasth Diwali campaign, National Clean Air Programme (NCAP), Graded Response Action Plan (GRAP), National Ambient Noise Monitoring Network Programme, Horn Not OK Please campaign, Scheme of Assistance for abatement of pollution, Scheme of Common Effluent Treatment Plants, standards for emission of environmental pollutants, water pollutants and noise pollutants, National Green Corps (NGC), Sewage Treatment Plants Effluent Discharge Standards, Recognition of Environmental laboratories under Environment (Protection) Act, Apex committee, SAMEER App, E-Track for Industries, Swachh Bharat Abhiyan, Namami Gange Programme, National Solar Mission and Pradhan Mantri Ujjwala Yojana etc. are the prime and prominent initiative steps taken by the Govt. which has brought fruit in one and more sections of the society putting the graph of harms produced by contaminants to plateau and/or negative slope.